1991
DOI: 10.1111/j.1600-0536.1991.tb01794.x
|View full text |Cite
|
Sign up to set email alerts
|

Euxyl K 400: a new sensitizer in cosmetics

Abstract: Euxyl K 400 is a preservative for cosmetics and toiletries containing 2 active ingredients, 1,2-dibromo-2,4-dicyanobutan and 2-phenoxyethanol. 2057 consecutive patients with contact dermatitis were patch tested with Euxyl K 400 2.5% pet. and ethanol. A positive patch test occurred in 24 patients (1.2%). The source of sensitization was traced in 8 patients to their cosmetics. Both leave-on and rinse-off products were responsible. Further patch tests with Euxyl K 400 0.5% pet. and phenoxyethanol 5% pet. were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 5 publications
0
38
1
1
Order By: Relevance
“…was not considered relevant (14). Further cases of allergic contact dermatitis associated with the use of rinse-off products have been reported (6,29). It can be concluded that, with regard to elicitation, the safe concentration of MDBGN in rinse-off products may lie between 200 and 1000 p.p.m., and probably closer to 200 p.p.m.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…was not considered relevant (14). Further cases of allergic contact dermatitis associated with the use of rinse-off products have been reported (6,29). It can be concluded that, with regard to elicitation, the safe concentration of MDBGN in rinse-off products may lie between 200 and 1000 p.p.m., and probably closer to 200 p.p.m.…”
Section: Discussionmentioning
confidence: 85%
“…It can be concluded that, with regard to elicitation, the safe concentration of MDBGN in rinse-off products may lie between 200 and 1000 p.p.m., and probably closer to 200 p.p.m. The actual permitted maximum concentration of (6). Analyses of leave-on products, which were considered to be relevant in MDBGN-allergic patients, contained 87 (1 product) to 399 p.p.m., with 8 products clearly >100 p.p.m.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Italian investigators, Tosti et al [17] (1988-1990) tested 2,057 consecutive patients with suspected contact dermatitis to Euxyl K400 2.5% pet. and ethanol.…”
Section: Frequency Of Contact Sensitisation To Euxyl K400mentioning
confidence: 99%